Gagasan Pengadilan Khusus Untuk Sengketa Hasil Pemilhan Kepala Daerah - Ayuni, Qurrata (Jurnal Hukum & Pembangunan, 2018)
The Constitutional Court in Decision Number 97 / PUU-XI / 2013 states that the dispute over the head of region election is not included in the authority of its constitutionality. The Lawmakers follow up this ruling by initiating a special judicial body that will hear disputes over the results of head of region election. Special judicial bodies should have been formed before the head of region election simultaneously. In the transitional period, before the establishment of a special judicial body, disputes over the results of head of region election are still handled by the Constitutional Court in 2015 and 2017. This study aims to seek and provide an overview of the options for the form and design of special courts of head of region election such as through the State Administrative High Court, Election Supervisory Board and remain in the Constitutional Court. This paper suggests the existence of a judicial body that will handle disputes over regional head elections that will provide legal certainty for the democratic process in Indonesia.